HUBUNGAN ANTARA GAYA KEPEMIMPINAN, SEMANGAT KERJA DAN PENGEMBANGAN KARIR DENGAN KINERJA KARYAWAN DI PT. AGUNG AUTOMALL CABANG BENGKULU - Andriyani Prawitasari; Doki Bustari (Creative Research Management Journal, 2020)
The purpose of this study is to find out a correlation between leadership style, spirit and career development with employee performanceat PT. Agung Automall Bengkulu Branch with the samples of 91 employees. Due to all the population in this study were sampled, the sampling method was by census. Data were collected using questionnaires and analyzed using Spearman rank correlation and hypothesis testing t test. Spearman rank test results there is a strong correlation between leadership style with employee performance at PT. Agung Automall Bengkulu Branch. This is reinforced by the results of hypothesis testing known to a significant, meaning that the leadership style has a positive and significant correlation with the performance of employees at PT. Agung Automall Bengkulu Branch. The results of the study for the correlation between spirit with employee performance at PT. Agung Automall Bengkulu Branch obtained a Spearman rank correlation with strong evaluation criteria. The results of the Spearman rank are also strengthened by the results of hypothesis testing with a significant, meaning that there is a significant correlation between organizational culture and performance.Career development has a moderate correlation with the performance of the employees of PT. Agung Automall Bengkulu Branch with Spearman rank correlation. This result is strengthened by testing the hypothesis with a significant, meaning that career development has a significant correlation with employee performance at PT. Agung Automall Bengkulu Branch.